2006
DOI: 10.1097/00006231-200606000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hand perfusion with 99mTc-HSA in patients expecting to undergo coronary bypass surgery: elaboration of a new complex diagnostic protocol for the safe removal of a radial artery graft

Abstract: Hand perfusion with (99m)Tc-HSA is useful in patients selected for coronary bypass operations, so we recommend the introduction of this method as a routine examination before the removal of the radial artery in patients with an abnormal Allen test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Even scintigraphy for screening palmer circulation has been suggested by Garai and colleagues. 18 It has further been shown that RA conduits otherwise considered acceptable for bypass grafting, were often found by optical coherence tomography to have a substantial amount of lipid, which strongly correlates with the risk of postoperative spasm. 19 Screening conduits based on characteristics of intimal quality may the improve the results of RA grafting, yet one has to keep logistics as cost-benefit issues in mind before advocating additional tests as routine for picking up just that one extra anecdotal case.…”
Section: Discussionmentioning
confidence: 99%
“…Even scintigraphy for screening palmer circulation has been suggested by Garai and colleagues. 18 It has further been shown that RA conduits otherwise considered acceptable for bypass grafting, were often found by optical coherence tomography to have a substantial amount of lipid, which strongly correlates with the risk of postoperative spasm. 19 Screening conduits based on characteristics of intimal quality may the improve the results of RA grafting, yet one has to keep logistics as cost-benefit issues in mind before advocating additional tests as routine for picking up just that one extra anecdotal case.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some clinicians espouse the use of more advanced preoperative testing. Specifically, Garai et al 28 recommend performing hand perfusion studies with the injection of technetium 99-m labeled human serum albumin in patients with an abnormal Allen's test to identify those who are truly at an increased risk of hand ischemia following radial artery harvest for coronary artery bypass grafting. An abnormal Allen's test is often defined as the inability of the hand to flush within 15 seconds after releasing occlusive pressure on the ulnar artery.…”
Section: Prevention and Managementmentioning
confidence: 99%